Markers of Metabolic Syndrome in Patients with Pituitary Adenoma: A Case Series of 303 Patients - Altuntaş, Seher Çetinkaya; Evran, Mehtap; Sert, Murat; Tetiker, Tamer (Hormone and Metabolic Research, 2019)
To assess the demographic characteristics and hormonal status of patients who presented to our clinic with pituitary adenoma and to demonstrate the presence, prevalence, and relationship of metabolic syndrome parameters in these patients. The study included 303 patients with known or newly diagnosed pituitary adenoma and 52 age- and sex-matched healthy controls. The patients were classified into 3 groups; acromegaly (ACRO) (n=54),prolactinoma (PRLoma) (n=163), and non-functional adenoma (NFA) (n=86). in 55.6% (n=172) and 52% (n=163) of the patients, respectively. The waist circumference of all patients (p<0.001) and body mass index (BMI) of patients with PRLoma (p=0.03) and ACRO (p<0.001) were found to be significantly higher than in the controls. The HbA1c, insulin and HOMA-IR values were significantly higher in the ACRO and PRLoma groups, whereas the insulin and HOMA-IR values were significantly higher in the NFA group compared with the control group (p<0.001 and p<0.001, respectively). When the 3 patient groups were compared, waist circumference and BMI were significantly higher in the ACRO group than in the PRLoma group (p=0.04 and p=0.03, respectively). In patients developing pituitary failure after treatment, age, waist circumference, plasma glucose, low-density lipoproteins and triglyceride values were significantly increased when compared with those without pituitary failure after treatment (p<0.001). In our study, it was found that there was increased metabolic and cardiovascular risk in functional pituitary adenoma and NFA.
Keywords: pituitary adenoma; non-functional adenoma; acromegaly